OUTSOURCING SUPPLY CHAIN: SYSTEMATIC LITERATURE REVIEW ON INNOVATION DRIVER FACTORS TOWARDS COLLABORATIVE NETWORK - Dini Hamidin; Rofi Rofaida (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2021)
Innovation and collaboration are essential to every organization in order to compete with its competitors. Outsourcing is done to distribute part of the responsibility of the parent organization so that it can be focused on its core business. The purpose of this literature review study is to determine innovation in collaborative networks related to the outsourcing supply chain. The SLR methodology was used in this study, while the database was taken from 6 sources, i.e., Emerald, Sage Journal, SpringerLink, IEEE, ScienceDirect, Wiley Online Library, and obtained 50 appropriate articles relevant to the topic. The literature review resulted that there are six trend innovations as collaboration network drivers. The future trends of innovation will be the dominance of research leading on three innovation trends, namely collaborative innovation, Innovation ecosystem, and open innovation in line with the development of technology and information disclosure.